Optimal water intake for the elderly: prevention of hypotremia (Faculty of Medicine Universitas Indonesia, 2009)
Aim The prevalence of hyponatremia in the elderly is quite high due to the rising of ADH and ANP concentrations which are part of eight physiologic changes. The complications are quite specific, among others, increased risk of bone fracture, declining of conciousness, and convulsion. The frequent cause of hyponatremia is high water intake. To achieve the optimal water intake designated as the highest water intake that did not cause hyponatremia and hypovolemia. Methods A study was conducted on 31 healthy elderly subjects, selected from 107 persons using simple random sampling and exclusion criteria. By block randomisation were classified into five water-intake groups (1000-2500 mL). Results In this study, it could be proved that 1000 mL was the optimal. It was also unraveled that the ADH levels had a role in determining the water intake volume that did not cause hyponatremia and NT-proBNP concentrations did not correlate with spot urine sodium. Conclusion The optimal water intake for the elderly is 1000 mL per day. (Med J Indones 2009; 18: 18-24) Keywords: Hyponatremia, healthy elderly, water intake